PENGARUH PROFITABILITAS, FINANCIAL DISTRESS, UKURAN PERUSAHAAN, REPUTASI AUDITOR DAN OPINI AUDIT TERHADAP AUDIT REPORT LAG Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia pada Periode Sebelum Pandemi (2017-2018) dan Periode Masa Pandemi (2019-2020) - Gabriella Cindy Ananda Alverina; Paulus Th. Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2022)
This study aims to examine the effect of profitability, financial distress, company size, auditor reputation and audit opinion on Audit Report Lag (ARL). The variables used in this study are profitability, financial distress, company size, auditor reputation and audit opinion as independent variables, and audit report lag (ARL) as the dependent variable.This empirical study uses manufacturing companies listed on the Indonesia Stock Exchange. Due to the Covid-19 pandemic, there were regulatory changes made by OJK, one of which was regarding the relaxation of the deadline for submitting annual financial reports that are valid for 2019 and 2020 for 2 months to 31 May. This has led to two research periods in this study, namely the period before the pandemic (2017-2018) and the period of the pandemic (2019-2020). Sampling was based on purposive sampling method with certain criteria. The total sample obtained was 230 companies with 16 outliers in the pre-pandemic period (2017-2018) and 260 companies with 26 outliers in the pandemic period (2019-2020). Multiple linear regression analysis is the analytical method used in this study.The results showed that in the period before the pandemic (2017-2018) profitability variables and company size had a significant negative effect on audit report lag, financial distress had a positive but not significant effect on audit report lag, and auditor reputation and audit opinion had a negative but not significant effect. to audit report lag. While in the pandemic period (2019-2020) the results show that profitability, company size, and audit opinion variables have a significant negative effect on audit report lag, financial distress has a positive significant effect on audit report lag, auditor reputation has a negative but not significant effect to audit report lag.